Assessment of dynamic wireless charging based electric road system: A case study of Auckland motorway. (September 2022) - Majhi, Ramesh Chandra; Ranjitkar, Prakash; Sheng, Mingyue
Highlights: Calibration, and validation of a part of Auckland traffic network using AIMSUN. Estimation of dynamic wireless charging length requirement in a traffic corridor. Impact of traffic and energy parameters on the wireless charging length requirement. Financial feasibility of DWC system with the plug-in charging system. Abstract: Urbanization and the need to improve green mobility have paved the way for electric vehicle (EV) adoption that reduces greenhouse gas emissions. Investors have a critical role in incentivizing charging infrastructure to meet EV's charging needs immediately. Dynamic wireless charging (DWC) offers a viable solution to mitigate issues related to the limited driving range, higher battery capacity (resulting in higher cost), and longer charging time of EVs. This paper examines the impact of a DWC-based electric road system (ERS) on EV flow and energy consumption. A traffic simulation-based methodological framework is developed to evaluate the effect of DWC facilities on road networks. A case study is conducted for the Auckland motorway network using various scenarios to evaluate the performance of the ERS, including the financial feasibility of the DWC system compared with the existing plug-in charging system. It provides insights into the minimum length of DWC facilities and the spatial and temporal variations in energy demand, which can be helpful to public and private stakeholders in deciding the optimal strategy to implement DWC in transportation networks on a large scale.